Implementasi Teknologi Blockchain pada Sistem Presensi Staff VM LePKom Berbasis Web - Ilham Wijaya; Emy Haryatmi; Ary Bima Kurniawan (InfoTekJar : Jurnal Nasional Informatika dan Teknologi Jaringan, 2020)
Attendance for staff is one of data collection in the institution as a part of reporting and recording activity. Blockchain technology or distributed ledger has become registration system used in the network. Blockchain technology is one of the technologies that has robust security system and minimizing the lost of data because each node has the copy of data. Blockchain technology can be implemented in many aspects for example in the attendance system in LePKom Gunadarma University based on virtualization. There is an attendance for staff application in LePKom using web application but the database used in the application is centralized. Using centralized database has many disadvantages such us the lost of data or data can be changed by others. The objective of this research is to analyze the implementation of blockchain technology for staff attendance based on web application in VM LePKom. Method of this research used System Development Life Cycle (SDLC). The result of this research was blockchain technology can be implemented in attendance application and distributed database. Data was secured using Proof of Work (PoW) consensus Algorithm and can be validated.